Practical characterology - Meredith, James C. (Statistical and Social Inquiry Society of Ireland, 1929)
A paper on Characterology needs some apology, I fear, if it is to be read to a Statistical and Social Inquiry Society such as this. No doubt characterologists are not in quite as unenviable a position as palmists, clairvoyants or spiritualists. They are not liable to be imprisoned or fined under the obsolete provisions of enactments originally directed against gipsies and witches. But that is not because practical characterology is regarded as worthy of very serious consideration?though not a few people imagine themselves to be fairly good amateur characterologists? but only because it is not regarded as mischievous, and so not worth considering at all. In the public mind charaeterologists are supposed to stand in much the same relation to psychologists as homeopathists, herbists and bone-setters stand to those whose names are to be found on the Medical Register. The object of this paper is to consider if characterology does not deserve some measure of definite recognition, and if it appears to do so, to offer some suggestions as to the statistical methods that should be employed as the basis of characterological research.
Read Nov. 15, 1928
Keywords: Personality types; Characterology; 314.15